2024
DOI: 10.2147/ijn.s441453
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Extracellular Vesicles Derived from Human Umbilical Vein Endothelial Cells Promote Skin Repair by Enhancing Angiogenesis: From Death to Regeneration

Jinzhao Liu,
Jia Dong,
Xibo Pei

Abstract: The promotion of angiogenesis is an effective strategy for skin wound repair. While the transplantation of endothelial cells has shown promise in vascularization, the underlying mechanism remains unclear. Recent studies have suggested that transplanted cells undergo apoptosis in a short period and release apoptotic extracellular vesicles (ApoEVs) that may have therapeutic potential. Methods: In this study, we isolated ApoEVs from human umbilical vein endothelial cells (HUVECs) and characterized their propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Although the interplay of HFSCs and ECs has less been reported under expanded condition, they indeed play a crucial role in epidermal regeneration because tissue regeneration deeply relies on neovascularization and re-epithelization. For example, in angiogenesis, which is vital for skin barrier rebuilding ( Liu et al, 2024 ), Heidari reported that HF bulge cells increased vascularization in full-thickness wounds in mice instead of HF isthmus cells ( Heidari et al, 2016 ). In the study conducted by Babakhani, when HFSCs were administered around the periphery of the wound, it was observed that the wound area exhibited significant enhanced neovascularization, particularly notable on the 7th and 14th days following treatments, in comparison to other groups ( Babakhani et al, 2020 ).…”
Section: Hfscs In Epidermal Regenerationmentioning
confidence: 99%
“…Although the interplay of HFSCs and ECs has less been reported under expanded condition, they indeed play a crucial role in epidermal regeneration because tissue regeneration deeply relies on neovascularization and re-epithelization. For example, in angiogenesis, which is vital for skin barrier rebuilding ( Liu et al, 2024 ), Heidari reported that HF bulge cells increased vascularization in full-thickness wounds in mice instead of HF isthmus cells ( Heidari et al, 2016 ). In the study conducted by Babakhani, when HFSCs were administered around the periphery of the wound, it was observed that the wound area exhibited significant enhanced neovascularization, particularly notable on the 7th and 14th days following treatments, in comparison to other groups ( Babakhani et al, 2020 ).…”
Section: Hfscs In Epidermal Regenerationmentioning
confidence: 99%